Evaluasi Pelaksanaan Kampanye Sosial Perilaku Hidup Bersih dan Sehat untuk Menurunkan Angka Diare di Kabupaten Kulonprogo - Tri Hastuti Nur Rochimah (Jurnal ILMU KOMUNIKASI, 2009)
Â Abstract: Even though the campaign of â€œPerilaku Hidup Bersih dan Sehatâ€ has become a very deep attention from government, mass organization and NGO in Indonesia for so long, this program is still ineffective. It is indicated by the increasing of diarrhea sufferers in Kabupaten Kulon Progo. It can be an impact of three factors: (1) inappropriate media and message strategy and (2) minimal political will of the government, and also (3) the campaign design is not based on the field research. Additionally, the approach of this campaign did not encourage people to participate.